Dicentrarchus labrax ... - Çiçek, Erdoğan; Fricke, Ronald; Sungur, Sevil; Çapar, Osman Bahadir; Golani, Daniel (Zenodo, 2023)
Dicentrarchus labrax (Linnaeus, 1758) [N]—European seabass; Labrak halak Taxonomy. Original description: Perca labrax Linnaeus, 1758: 290 [Southern Europe, Mediterranean Sea; syntypes: BMNH 1853.11.12.1 (1, skin)].— Israel synonyms: Morone labrax (Linnaeus, 1758).—Revisions: None.—Illustration: Tortonese in Whitehead et al. (1986: 794, fig.). Status in Israel. First record in freshwater from Israel by Yashouv (1969); confirmed by Goren & Ortal (1999), Golani & Mires (2000).—Israel material: HUJ. Distribution and habitat. Distribution in Israel: Mediterranean watersheds.—Distribution in River Basin: 1- Western Basin, 2-Dead Sea Basin.—General distribution: Western Baltic Sea; North Sea; Mediterranean Sea; Sea of Marmara; Black Sea; Eastern Atlantic: Norway and Iceland south to Senegal, including Madeira; Red Sea: Gulf of Suez (Mediterranean Sea immigrant).—Distribution in Ecoregion: 436-Coastal Levant, 438- Jordan River.— Habitat: This species is pelagic, near shore, and sometimes in lagoons and ... : Published as part of Çiçek, Erdoğan, Fricke, Ronald, Sungur, Sevil, Çapar, Osman Bahadir & Golani, Daniel, 2023, Freshwater fishes of Israel; a revised and updated annotated checklist- 2023, pp. 451-484 in Zootaxa 5369 (4) on pages 474-475, DOI: 10.11646/zootaxa.5369.4.1, http://zenodo.org/record/10146651 ...